Digital Skills Development and Workforce Innovation: A Systematic Review of Human Capital Management in Education - Zulbilal, Ahmad; Torrido, Aryan; Mardiyah, Mardiyah (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
The rapid technological transformation in the 21st century has brought fundamental changes to the world of education, requiring educators to master digital skills and be adaptive to technological changes. Human Resource Management (HCM) is a relevant strategic framework to support the development of digital skills and workforce innovation in education. This study aims to explore trends, challenges, and opportunities in digital skills development through the HCM approach. Using a systematic literature review method based on the PRISMA protocol, 20 articles published between 2019–2024 were analyzed with a focus on "Digital Skills Development," "Human Capital Management," and "Workforce Innovation" in the context of social sciences and learning. The results of the study identified key challenges, including limited technological infrastructure, lack of teacher training, and policy gaps, as well as opportunities such as the integration of digital competencies into the curriculum, the development of data-driven assessment tools, and cross-sector collaboration. This study shows trends in strengthening teachers' digital skills, data-driven workforce management, and educational innovation to support workforce readiness. This research provides strategic recommendations in the form of strengthening data-based policies, continuous teacher training, and developing an inclusive digital curriculum, while also offering opportunities for further research to address the challenges of education in the digital era.